1990
DOI: 10.1210/jcem-71-1-235
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prostaglandin Synthetase Inhibitors on Human Preovulatory Follicular Fluid Prostaglandin, Thromboxane, and Leukotriene Concentrations*

Abstract: This study evaluates the eicosanoid concentration in luteinized unruptured follicles (LUFs) on the ovaries of patients who had been treated with inhibitors of prostaglandin synthetase. Indomethacin, bromfenac, or azapropazone (or a placebo) was administered orally to 41 women during the periovulatory period. Follicular development was monitored by serial ultrasound examinations, and the onset of ovulation was regulated by an injection of hCG. Follicular fluid was aspirated during sterilization by minilaparotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Intrafollicular PGF 2 a, PGFM, and PGE 2 were consistently decreased in mares of the induced LUF group. Similar results have been shown in the follicular fluid of women treated with various NSAIDs (Priddy et al 1990). Prostaglandins are vital for the ovulatory process in vertebrates (reviewed in Murdoch et al (1993)).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Intrafollicular PGF 2 a, PGFM, and PGE 2 were consistently decreased in mares of the induced LUF group. Similar results have been shown in the follicular fluid of women treated with various NSAIDs (Priddy et al 1990). Prostaglandins are vital for the ovulatory process in vertebrates (reviewed in Murdoch et al (1993)).…”
Section: Discussionsupporting
confidence: 73%
“…Likewise, higher plasma E2 concentrations have been described in women with spontaneous LUFs (Hamilton et al 1985). However, no differences in intrafollicular E2 concentrations were previously documented in women following NSAID treatment (Priddy et al 1990). Estradiol-mediated stimulation of PGE 2 synthesis in preovulatory follicles in mice (Toda et al 2012) may explain the increased PGE 2 :PGF 2 a ratio in mares of the induced LUF group.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The reason why bromfenac sodium possesses inhibitory activity in VKC recurrence is unclear from our study. However, it has been reported that systemic bromfenac treatment significantly reduces not only PGE 2 and PGF 2 α levels in the follicular fluid, but also LTB 4 levels compared with those after placebo treatment in humans [25]. The LTB 4 level in tears of patients with VKC is reported to be elevated [26].…”
Section: Discussionmentioning
confidence: 99%